Hard to Swallow: Remembering to Check for Impacted Dentures in Elderly Patients Presenting with Swallowing Difficulty - Ramesh, Priyavarshini; Morgan, Cerys; Fertleman, Michael; Koizia, Louis John (Archives of Clinical and Biomedical Research, 2023)
Background: Swallowing difficulty is a common issue associated with hospital admission and can be due to a variety of causes, including accidental ingestion of dentures. This case highlights the importance of ensuring aids such as dentures are accounted for early in elderly patients presenting with swallowing difficulty before subjecting them to medical treatment and investigations for other causes. Case Presentation: We present the case of a woman in her late 80s who was originally admitted for pelvic fractures and developed new dysphagia and odynophagia with associated voice hoarseness and pooling of saliva. She was initially treated for supraglottitis with antibiotics and dexamethasone with minimal response. Following administration of glycopyrronium, her dentures were visualised in the hypopharynx, and removed. The patient was able to recover her swallow and return to baseline oral intake. Conclusions: This case highlights the importance of accounting for aids commonly used in the elderly including dentures and ensuring that their presence or absence is documented to prevent misdiagnosis.